2012
DOI: 10.1590/s1984-70332012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and correlation among potato tuber traits

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Breeders can generally achieve genetic gain when selected individuals have a better genotypic profile than unselected individuals (i.e., a better combination of alleles involved in the genetic determinism of the trait of interest). The best conditions to optimize the response to selection are: high phenotypic variation, high heritability, and high selection pressure (Bisognin et al, 2012). It is possible to benefit from all genetic effects (additive, dominance, and epistatic effects) when considering selection for clonally propagated crops.…”
Section: Methodsmentioning
confidence: 99%
“…Breeders can generally achieve genetic gain when selected individuals have a better genotypic profile than unselected individuals (i.e., a better combination of alleles involved in the genetic determinism of the trait of interest). The best conditions to optimize the response to selection are: high phenotypic variation, high heritability, and high selection pressure (Bisognin et al, 2012). It is possible to benefit from all genetic effects (additive, dominance, and epistatic effects) when considering selection for clonally propagated crops.…”
Section: Methodsmentioning
confidence: 99%
“…Mean values were used to nd the correlation among the traits. According to Bisognin et al (2012), tuber shape is related to average tuber weight. Similarly, Khayatnezhad et al (2011) discovered a highly signi cant correlation (r = 0.99) between average tuber weight and average tuber yield similar to our results like SFW and SDW (r = 0.98), ATY and ATW (r = 0.69), ATY and TNT (r = 0.72) showed a strong correlation (Fig.…”
Section: Analysis Of Phenotypic Traitsmentioning
confidence: 99%
“…For potato, heritability in the broad sense is of greater importance, as the effects of dominance and epistasis are sustained in successive generations by clonal propagation (Howard, 1978). Selection of quality clones for industrial processing would be facilitated by information on the inheritance of the characters that compose it, and although several studies on heritability in both clone and family have been reported Salamoni et al (2000), heritability estimates are unique, depend on the genetic diversity of the material tested and are strongly influenced by growing conditions (Bisognin et al, 2012). In addition, the existence of genotype-environment interaction may reduce the industrial quality character selection response (Hayes and Thill, 2003), and selection of clones based on evaluation in different production environments is required, however, most heritability and selection response studies for industrial processing quality traits are directed to distinct growing conditions from Brazil (Hayes and Thill, 2003;Bisognin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%